EFEKTIVITAS TABLET TAMBAH DARAH DAN EKSTRAK KACANG HIJAU PADA PENINGKATAN HEMOGLOBIN REMAJA PUTRI - Linda Suryani; Mustika Hana Harahap; Violita Dianatha Puteri (LPPM Universitas Abdurrab, 2025)
Adolescent girls are at high risk of developing anemia due to significant iron requirements, which are exacerbated by menstruation, poor dietary patterns, worm infections, the habit of drinking tea or coffee after meals, lack of sleep, vitamin C deficiency, and economic circumstances. In addition to consuming iron supplements, the prevention and treatment of anemia can be achieved through a balanced diet, including drinking mung bean extract, which is rich in iron and vitamin C and can increase hemoglobin levels. This study employed a quasi-experimental method with a pretest-posttest two-group design at SMAN 2 Pekanbaru to analyze the effect of the combination of blood-boosting tablets and mung bean extract on increasing hemoglobin levels in 32 adolescent girls who exhibited symptoms of anemia and low hemoglobin levels (<12 gr/dl). The samples were divided into two groups: the intervention group (blood-boosting tablets + mung bean extract) and the control group (blood-boosting tablets only), each consisting of 16 individuals. The research findings indicated a significant increase in hemoglobin in both groups after the intervention. However, the group that consumed mung bean extract and blood-boosting tablets experienced a higher increase in hemoglobin levels (1.553 gr/dl) compared to the control group (1.017 gr/dl), with a statistically significant difference (p=0.020). The importance of health education by healthcare professionals and related institutions regarding the potential of mung bean extract as an alternative for anemia prevention in adolescent girls is emphasized. Routine hemoglobin level checks, particularly in adolescent girls, also need to be conducted more frequently..